Comprehensive auricular acupoint operation technique in the treatment of insomnia in an elderly patient with liver depression and spleen deficiency syndrome (耳穴综合操作技术治疗1例老年肝郁脾虚证失眠的护理体会) - GUO Huanli (郭换利); FENG Wenying (冯文英); ZHANG Guohong (张国红); HUANG Yanping (黄砚萍) (中西医结合护理, 2024)
This article summarized the nursing of a patient with insomnia caused by liver depression and spleen deficiency syndrome treated with comprehensive auricular manipulation techniques. According to the nursing assessment and Traditional Chinese Medicine syndrome differentiation, comprehensive auricular manipulation techniques including auricular massage, ear tip bloodletting and auricular acupoint pressing therapy, combined with emotion regulation, were carried out relieve the negative emotion and improve the sleep quality of the patient. (本文总结1例耳穴综合操作技术治疗肝郁脾虚证失眠的护理体会。根据护理评估和中医辨证, 采取耳部按摩、耳部放血、耳穴贴压综合疗法, 并配合情志护理, 有效缓解患者负性情绪, 改善了患者睡眠质量。)